1994
DOI: 10.1080/09670269400650551
|View full text |Cite
|
Sign up to set email alerts
|

Minimum spectral light requirements and maximum light levels for long-term germling growth of several red algae from different water depths and a green alga

Abstract: Spores and germlings of six red algal species were cultivated for 15 weeks in coloured light fields at low intensities. The photon fluence rates at which growth exceeded growth in dark-kept controls were, in green light, 0-1 #mol m-2s -1 in Audouinella daviesii, 0.5 #mol m-2s -1 in Halarachnion ligalatum, Pterothamnion plumula, Chondrus crispus and Plumaria elegans, and I'0/~mol m-2s -~ in Ceramium rubrum. In blue or red light, at least 1-0 #mol m-2s -1 was required for germling growth in these species, except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 39 publications
0
13
2
Order By: Relevance
“…). While our estimates for A. crinitum are somewhat lower than previously published results, given the good agreement between two separate lines of evidence (i.e., photosynthesis and growth experiments) and that the minimum daily light requirements of some rhodophyte macroalgae can be very low (0.01–0.03 mol photons · m −2 · d −1 ; Leukart and Lüning ) it seems likely that the these minimum daily light requirements for A. crinitum are realistic. Collectively these low minimum light requirements for photosynthesis and growth suggest that A. crinitum is well adapted to harvesting low incident light and supports our conclusion that A. crinitum is a highly shade tolerant species and a functional analog of rhodophyte algae in other deep‐water or low light habitats.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…). While our estimates for A. crinitum are somewhat lower than previously published results, given the good agreement between two separate lines of evidence (i.e., photosynthesis and growth experiments) and that the minimum daily light requirements of some rhodophyte macroalgae can be very low (0.01–0.03 mol photons · m −2 · d −1 ; Leukart and Lüning ) it seems likely that the these minimum daily light requirements for A. crinitum are realistic. Collectively these low minimum light requirements for photosynthesis and growth suggest that A. crinitum is well adapted to harvesting low incident light and supports our conclusion that A. crinitum is a highly shade tolerant species and a functional analog of rhodophyte algae in other deep‐water or low light habitats.…”
Section: Discussioncontrasting
confidence: 49%
“…Existing syntheses of experimentally derived physiological data, observed maximum depth limits and light attenuation coefficients suggest that minimum daily light requirements for macroalgal growth must lie somewhere between 0.0001 (crustose coralline algae) and 4.42 mol photons Á m À2 Á d À1 (Valonia ventricosa, Chlorophyta; Littler et al 1986, L€ uning 1990, Markager and Sand-Jensen 1992, Spalding et al 2003, Gattuso et al 2006, Kirk 2011, with the minimum light requirements for non-calcareous rhodophyte macroalgae near 0.91 mol photons Á m À2 Á d À1 (Gattuso et al 2006). While our estimates for A. crinitum are somewhat lower than previously published results, given the good agreement between two separate lines of evidence (i.e., photosynthesis and growth experiments) and that the minimum daily light requirements of some rhodophyte macroalgae can be very low (0.01-0.03 mol photons Á m À2 Á d À1 ; Leukart and L€ uning 1994) it seems likely that the these minimum daily light requirements for A. crinitum are realistic. Collectively these low minimum light requirements for Letters denote significant differences between light levels and asterisks denote a significant difference compared to initial values.…”
Section: Survival Under Low Lightcontrasting
confidence: 51%
“…In Lake Tovel, algal biomass is low [ Cellamare et al ., ], and most of the phytoplankton community is composed of mixotrophs (chrysophytes, cryptomonads, and dinoflagellates) and osmotrophs (diatoms) that are adapted to low light and cold temperatures [ Flaim et al ., ; Cellamare et al ., ]. While under‐ice PAR intensity at 5 m was low (mean = 7.4 µmol photons m −2 s −1 ; median = 1.8), these observed low light intensities were within the range that enables photosynthetic activity in algae adapted to deep waters [see Leukart and Lüning , ; Gomez et al ., ]. Thus, assuming photosynthetic activity under ice seemed reasonable and probably occurred at a higher rate above a depth of 5 m.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, some studies have shown that B and G light could play an advantageous role on red algae growth and their development [19]. Moreover, Pearson et al [20] reported that Silvetia compressa releases gametes during B or in low R/B light ratios exposure, showing significant influences of light wavelength on algal growth.…”
Section: Discussionmentioning
confidence: 99%